BRONCHIECTASIS IN CHILDREN WITH PCD: MPA (MAIN PULMONARY ARTERY) AND MPA-TO-AA RATIO AS MARKERS OF DISEASE SEVERITY - Zafar, Adnan; Qureshi , Mohammed Salman; Ayub, Saba (Journal of Ayub Medical College Abbottabad, 2025)
Objective Lung function in primary ciliary dyskinesia becomes abnormal from an early age and doing any lung function test in the first few years of life requires a child’s cooperation which can be difficult. HRCT is done every few years to monitor lung structure. We aimed to look at the relationship of bronchiectasis with the size of MPA (main pulmonary artery) and MPA-to-AA (ascending aorta) ratio. This can be used as an additional disease marker when assessing CT chest. Methods This was a retrospective analysis of CT chest measurements in children with confirmed PCD, followed up at our centre between 2008-2020. Diameters of the main pulmonary artery, ascending and descending aorta were measured at predetermined reference points. The scans were independently analysed by two radiologists. CT chest contrast images were obtained on a 64 slice- Discovery CT750 HD, GE Healthcare medical system. Bronchiectasis was graded using the Modified Reiff scoring method. Results 38 measurements from 26 patients were taken into consideration to assess the relationship between MPA diameter, MPA: Ascending aorta and bronchiectasis. There was a positive correlation between the age-adjusted MPA-to-AA ratio and severe bronchiectasis (r=0.59, p=0.47). Children without bronchiectasis had an inverse correlation with MPA-to-AA ratio (r= -0.28, p=0.16). MPA diameter was positively related to both severe (r=0.59, p=0.06) and no bronchiectasis (r=0.91, p=0.01). There was a disproportionate age-dependent increase in the size of MPA in children who had multiple scans once bronchiectasis progressed from mild to severe. Conclusions This is a pioneer study looking at CT chest markers like MPA (diameter) and MPA-to-AA ratio in children with PCD and their relevance to the severity of bronchiectasis. An elevated MPA-to-AA ratio can be used as a marker of severe bronchiectasis however MPA diameter on its own has limited value in differentiating mild from severe bronchiectasis.